Embryo Disposition, Divorce & Family Law Contracting: A Model for Enforceability - Forman, Deborah L. (Columbia Journal of Gender and Law, 2013)
Courts, legislatures, and scholars have struggled with how to resolve disputes between progenitors of cryopreserved embryos in the event of divorce. This Article considers whether contracts entered into by the couple regarding disposition prior to divorce should be enforced and, if so, under what circumstances. The Article answers this question by taking a multidisciplinary perspective, incorporating insights from the social science literature, and by situating embryo disposition contracts in the broader context of other family law contracts, including donor, surrogate, co-parenting, premarital and postmarital contracts, with special consideration of the gender issues embedded in these approaches. The Article argues that existing treatment of these various family law contracts lends ample support for finding embryo disposition contracts enforceable, but also demands that embryo disposition contracts satisfy certain procedural protections to ensure careful consideration and thorough understanding of the complexities of the issue by the parties.